Production of Biogas and Alcohol from Aloe barbadensis Miller - Nagaraju, M.; Ramulla, Suhas; Murthy, N.Y.S. (Asian Journal of Chemistry, 2010)
Biogas is an alternate of fuel produced by the action of various groups of anaerobic bacteria on biomass, manure, sewage, municipal waste and green waste. It useful for cooking and for electricity production. Production of biogas and alcohol from the rind of Aloe barbadensis Miller is presented in this communication.